Practical Software Engineering Capstone Course – Framework for Large, Open-Ended Projects to Graduate Student Teams - Vasankari T.; Majanoja A. (Switzerland, 2025)
For students, capstone project represents the culmination of their studies and is typically one of the last milestones before graduation. Participating in a capstone project can be an inspiring learning opportunity or a struggle due various reasons yet a very educative learning experience. During the IT capstone project students practice and develop their professional skills in designing and implementing a solution to a complex, ill-defined real-life problem as a team. This paper reflects on organizing IT capstone projects in computer science and software engineering Master programmes in a Sino-Finnish setup, where the projects are executed in a framework provided by a capstone project course. We describe the course framework and discuss the challenges in finding and providing ill-defined challenges with meaningful real-life connection for project topics. Based on our observations complemented with students’ feedback we also propose areas for future development.
Computer Supported Education: 10th International Conference, CSEDU 2018, Funchal, Madeira, Portugal, March 15–17, 2018, Revised Selected Papers